If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + -1 = -4p + -19 Reorder the terms: -1 + 2p = -4p + -19 Reorder the terms: -1 + 2p = -19 + -4p Solving -1 + 2p = -19 + -4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '4p' to each side of the equation. -1 + 2p + 4p = -19 + -4p + 4p Combine like terms: 2p + 4p = 6p -1 + 6p = -19 + -4p + 4p Combine like terms: -4p + 4p = 0 -1 + 6p = -19 + 0 -1 + 6p = -19 Add '1' to each side of the equation. -1 + 1 + 6p = -19 + 1 Combine like terms: -1 + 1 = 0 0 + 6p = -19 + 1 6p = -19 + 1 Combine like terms: -19 + 1 = -18 6p = -18 Divide each side by '6'. p = -3 Simplifying p = -3
| (2y-5)-8+y=5 | | 80=(x+9)+(6x-6) | | x^2-42xy-343y^2=0 | | 48=(14x+4)+(24x+2) | | 2b^2+7b=15 | | 2(4p+8)=128 | | x^2+3x-7=0 | | x^2-98=0 | | 2x^2-13x-7=0 | | 4(n+1)+2n=22 | | 3x^2+22x=-40 | | 5x-4=4-3x | | 9-2y=15-8y | | 5y+3=13 | | 2f=f+3 | | 2+2x=-10+5x | | -2x+8y=12 | | -9+2(4g-7)=-12 | | 3y-5=y-9 | | 3m+1=7m-15 | | 3(8-a)=(90-3a) | | 3(8-a)=18(5-3a) | | w+9=5w+5 | | 5y+7=7y-3 | | 10w+19+3w=6(9+w)-14 | | 3x(8-a)=18x(5-3a) | | 5x+2y=-17 | | -6x-2y=24 | | 2x(a+c)= | | 3x^4-15x^3+6x^2-30x=0 | | 3x^4-15x^3+6x^2-30=0 | | 10d-15=12d |